The Influence of Lifestyle, Service Quality, and Perceived Quality toward Purchase Decision of Fast Food in Malang City - nisa, Khoirun; Moeljadi, H. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the effects of Lifestyle, Service Quality, and Perceived Quality toward Purchase Decision of fast food on fast food consumer in Malang City. This research used 170 respondents as samples which were obtained from fast food consumer population at Malang City. Samples were obtained by using Accidental sampling method. Analysis tools that were used to test instruments in this research were validity and reliability test. Data analysis method that was used in this research is multiple regression method. In this research classical assumption test was performed to test the regression model. Hypothesis test used F test (Simultaneous test) and T test (Partial test). Result showed that Lifestyle, Service Quality and Perceived Quality as simultaneously had positive effect toward purchase decision of fast food (F count 20.575 > F table 2.10). Partially result showed that Lifestyle had positive effect toward purchase decision of fast food (T count 2.395 > T table 1.6643), partially result showed that Service Quality had positive effect toward purchase decision of fast food (T count 2.327 > T table 1.6643), and Perceived Quality had positive effect toward Purchase Decision of fast food (T count 4.537 > T table 1.6643). Perceived Quality had dominant effect toward Purchase Decision of Fast food in Malang City. Keywords: Lifestyle, Service Quality, Perceived Quality, Purchase Decision